2014
DOI: 10.1093/jac/dku065
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity and post-antibiotic effects of colistin in combination with other antimicrobials against colistin-resistant KPC-producing Klebsiella pneumoniae bloodstream isolates

Abstract: Combinations of colistin plus rifampicin, and less frequently tigecycline, exhibited synergistic activity in vitro against colistin-resistant KPC-Kp strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 33 publications
7
37
0
2
Order By: Relevance
“…1). As in previous studies (18,20,21,32,33), the mgrB region of these 8 strains was interrupted by IS10R and IS5-like elements. To demonstrate an effect on mgrB expression after IS element insertion in the promoter, the expression of mgrB mRNA was quantified by RT-qPCR, and the expression of mgrB was significantly reduced in those 5 strains (Table 1).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…1). As in previous studies (18,20,21,32,33), the mgrB region of these 8 strains was interrupted by IS10R and IS5-like elements. To demonstrate an effect on mgrB expression after IS element insertion in the promoter, the expression of mgrB mRNA was quantified by RT-qPCR, and the expression of mgrB was significantly reduced in those 5 strains (Table 1).…”
supporting
confidence: 72%
“…Modification of Ara4N is achieved by the pmrHFIJKLM operon (13), and the two-component systems PhoPQ and PmrAB with connector PmrD are involved in the regulation of the pmrHFIJKLM operon (16,17). Moreover, MgrB is a negative regulator that influences PhoQ-PhoP phosphorylation (18)(19)(20). In this study, we analyzed capsular type and multilocus sequence type (MLST) distribution of colistin-resistant K. pneumoniae in Taiwan and attempted to define the mechanisms of resistance to colistin.…”
mentioning
confidence: 99%
“…This is consistent with previous in vitro studies that indicated synergy between polymyxins and rifampin against KPC-producing K. pneumoniae (21)(22)(23)(24). However, beyond 24 h, our analyses revealed that clinically achievable free-drug concentrations were unable to provide a sustained reduction in the bacterial burden.…”
Section: Discussionsupporting
confidence: 90%
“…KPC enzyme expression, a common mechanism of resistance among carbapenemresistant Enterobacteriaceae, has further compounded the antibiotic resistance crisis, resulting in the increased use of polymyxins (22,23). Recently, increasing numbers of reports of polymyxin resistance in strains that were previously susceptible have clinicians worried, as they could potentially be faced with the challenge of having virtually no therapeutic alternatives (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical benefit of adding a carbapenem to the polymyxin is not apparent in infections due to KPC-Kp with elevated carbapenem MICs (Ն16 mg/liter) (10). Interestingly, rifampin-containing combination regimens to combat KPC-Kp have shown promise in preclinical animal models and some in vitro studies (11)(12)(13). However, optimized combination regimens involving polymyxins, carbapenems, and rifampin have yet to be fully elucidated.…”
mentioning
confidence: 99%